Estudo das propriedades fotoluminescentes de pós e filmes finos de MgTiO3 obtidos pelo método dos precursores poliméricos - Ferri, Elídia Aparecida Vetter (Universidade Federal de São Carlos, 2011)
In this study, MgTiO3 (MTO) powders and thin films that crystallize in a perovskite ilmenite crystalline structure were obtained and characterized. MTO were synthesized by the polymeric precursor method (PPM), which allows obtaining structurally ordered and disordered structures. In addiction, the photoluminescent properties were investigated as a function of the heat treatment temperature. MTO powders were heat treated at several temperatures ranging from 400 to 1300 °C for 2 h and characterized by X-ray diffraction (XRD), Micro Raman (MR) spectroscopy, termogravimetric and termodifferential analysis (TA), X-ray absorption near edge structure spectroscopy (XANES), ultraviolet-visible spectroscopy (UV-Vis), field emission gun scanning electron microscopy (FEG-SEM) and photoluminescence spectroscopy (PL). These techniques allowed observing the evolution of the phases, morphology as well as the structural order and disorder of the MTO samples. XRD and TA results indicated that the MTO ordered and pure phase was obtained at 600 °C. The photoluminescent property of structurally ordered and disordered MTO powders were studied at room temperature, using the excitation wavelength of 350.7 nm. Structurally disordered MTO present broad PL band of emission, while ordered MTO present a photoluminescent emission in red and infrared region of the spectra due to the tilt between complex clusters. XANES spectra showed in the disordered powders the coexistence of sixfold and fivefold titanium coordination. A correlation between the coexistence of these two types of coordination for the titanium atoms and PL was proposed. MTO thin films were obtained by spin coating of the polymeric solution on Pt/Ti/SiO2/Si substrates using a rotation speed of 7000 rpm, for 30 s and heat treated at temperatures ranging from 400 to 700 °C. MTO thin films properties were investigated by XRD, UV-vis, MR, atomic force microscopy (AFM) and PL measurements. It was verified that MTO thin films began to crystallize at 550 °C, characterized by the presence of (110) diffraction peak of the MTO structure. The analysis of experimental techniques was possible to correlated PL properties with order-disorder at short and long range and the MTO thin films morphology.
Study of the photoluminescent properties of MgTiO3 powder and thin films obtained by the polimeric precursor method
Keywords: Fotoluminescência; Titanato de magnésio; Filmes finos; Método dos precursores poliméricos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA